Mobile Phone Text Messaging Cross Platform Intervention for Cervical Cancer Screening: Changes in Knowledge and Attitude in Rural Areas Pre-Post Intervention - Niken Bayu Argaheni; Firman F Wirakusumah; Maringan D.L. Tobing; Herry Herman; Deni K. Sunjaya; Yudi Mulyana Hidayat (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
The key to the success of cervical cancer control programs is screening followed by adequate treatment. The socio-economic status gap and the low level of education lead to limited awareness and understanding of women of childbearing age. Increasing the capacity of knowledge of women of childbearing age through health education either directly or indirectly is important. Therefore, there is need to develop health education by utilizing the rapidly growing media today such as through the application of cross platform messages on smartphones. This study aims to analyze the effect of the application of health education on detection of cervical cancer through the application of cross-platform messages to increase knowledge and attitude of Women in Childbearing Age. A quasi-experimental research of pre-posttest design with control groups conducted consisting of 72 subjects of Women in Childbearing Age. Fogg's Behavior Model was the conceptual framework that guided the development of the cross-platform messaging intervention. A series of checklist from expert panel conducted to inform the development of the cross-platform messaging intervention. The messages are delivered for a 7-day period in the morning. Data collection using a checklist instrument. Univariable analysis through Rasch and bivariable modeling using numerical categorical comparative test, difference using T test. Findings revealed a significant increase in participants’ knowledge and attitude of cervical cancer screening. Women of Childbearing Age whose health education through cross-platform application has a 3.5 times probability of knowledge and good attitude compared to women of childbearing age who are not getting health education through cross-platform applications. Health education through cross-platform messaging services can be a cheap and effective method to improve the knowledge and attitude of women of childbearing age, as well as reaching individuals who have never done early detection of cervical cancer.